2011
DOI: 10.1002/hyp.7985
|View full text |Cite
|
Sign up to set email alerts
|

Fracture aperture reconstruction and determination of hydrological properties: a case study at Draix (French Alps)

Abstract: International audienceWe propose two techniques for fracture aperture reconstruction. The first one is a correlation technique that estimates the normal aperture or the tangential shift across a discontinuity whose sides present geometrical similarities. The only required material is a pair of appropriately controlled images of each side. Here, the images are maps of the corresponding side topography, obtained from laser profilometry. Assuming a purely normal opening, it is possible, from two corresponding sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…These observations suggest that the possible rapid flow pathways may occur through transmissive discontinuities. This is in agreement with fracture aperture reconstructions in these marls suggesting that the overall permeability is significant (Neuville et al , 2011b). The borehole geophysical data and images allowed evidencing several types of discontinuities in the marls, some of which may be transmissive and may play a role in rapid water flow circulation described above.…”
Section: Discussionsupporting
confidence: 90%
“…These observations suggest that the possible rapid flow pathways may occur through transmissive discontinuities. This is in agreement with fracture aperture reconstructions in these marls suggesting that the overall permeability is significant (Neuville et al , 2011b). The borehole geophysical data and images allowed evidencing several types of discontinuities in the marls, some of which may be transmissive and may play a role in rapid water flow circulation described above.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, more realistic models of fractures have been proposed, which often consist in one of the two following models: the void between two identical self‐affine fracture surfaces, opened and shifted with respect to each other, or the void between two statistically independent self‐affine surfaces. Both geometries have been observed, for example, in natural cases, like the joints present at depth in a marl formation analysed in Draix (Neuville et al . 2011a,b).…”
Section: Introductionmentioning
confidence: 77%
“…The determination of the detailed morphology of the open volume in a fracture or a joint is difficult to perform in situ , and seldom done beyond the characterization of an average aperture. Recently, we have performed such a study on a natural example of rock (black marl) analysed from a log core, and indeed found some example of self‐affine aperture fields at the scale of observation (10 cm) (Neuville et al 2011a,b).…”
Section: Aperture and Flow Modelmentioning
confidence: 93%
See 1 more Smart Citation
“…[6] Different reconstruction techniques have been used to quantify aperture fields in efforts to: (i) relate fracture surface roughness to fracture aperture [Brown, 1995;Lanaro, 2000]; (ii) quantify characteristics of fractures that intercept boreholes [Tatone and Grasselli, 2012;Neuville et al, 2012]; and (iii) understand how surface roughness may influence the hydraulic [Durham and Bonner, 1994] and mechanical [Brown and Scholz, 1986;Sharifzadeh et al, 2008] properties of fractures. In addition, these reconstruction techniques provide the potential to quantify changes in fracture aperture induced by mechanical and chemical processes [Durham et al, 2001;Yasuhara et al, 2006;Elkhoury et al, 2013].…”
Section: Introductionmentioning
confidence: 99%